2009
DOI: 10.1074/jbc.m804280200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epidermal Growth Factor Receptor Signaling in Human Cancer Cells by MicroRNA-7

Abstract: The epidermal growth factor receptor (EGFR) is frequently overexpressed in cancer and is an important therapeutic target. Aberrant expression and function of microRNAs have been associated with tumorigenesis. Bioinformatic predictions suggest that the human EGFR mRNA 3-untranslated region contains three microRNA-7 (miR-7) target sites, which are not conserved across mammals. We found that miR-7 down-regulates EGFR mRNA and protein expression in cancer cell lines (lung, breast, and glioblastoma) via two of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
336
3
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(366 citation statements)
references
References 48 publications
25
336
3
2
Order By: Relevance
“…It has been reported that miR-7 has a tumorsuppressor role in various cancers including brain tumors, breast cancer and lung cancer (Kefas et al, 2008;Reddy et al, 2008;Webster et al, 2009), and we herein showed that miR-7 also functions as a tumor suppressor in gastric cancer. Interestingly, in the normal stomach, miR-7 expression is induced during the differentiation of gastric epithelial cells, suggesting a role of miR-7 in the regulation of epithelial cell differentiation.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…It has been reported that miR-7 has a tumorsuppressor role in various cancers including brain tumors, breast cancer and lung cancer (Kefas et al, 2008;Reddy et al, 2008;Webster et al, 2009), and we herein showed that miR-7 also functions as a tumor suppressor in gastric cancer. Interestingly, in the normal stomach, miR-7 expression is induced during the differentiation of gastric epithelial cells, suggesting a role of miR-7 in the regulation of epithelial cell differentiation.…”
Section: Discussionsupporting
confidence: 66%
“…We found the expression level of miR-7 to significantly decrease in gastric tumors in an inflammation-dependent manner. It has been shown that miR-7 has a tumor-suppressor role in several cancers, including glioblastoma, breast cancer and lung cancer (Kefas et al, 2008;Reddy et al, 2008;Webster et al, 2009;Jiang et al, 2010;Saydam et al, 2011). In this manuscript, we demonstrate that miR-7 is induced during the differentiation of normal gastric epithelial cells, and it also has a tumor-suppressor role in the stomach.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…27 Recent studies demonstrated that EGFR may be a functional target of miRNAs. 28,29 MiRNA-128, which is frequently deleted in lung cancers, directly downregulated EGFR, but did not correlate with EGFR mutation and prognosis. Overall, all these studies suggest that miRNAs can be used as diagnostic and prognostic markers of lung cancer.…”
mentioning
confidence: 90%
“…In addition, it still positively regulates miR-7 (Reddy et al, 2008), which was found to control epidermal growth factor receptor signaling and promote photoreceptor differentiation, inducing cell cycle arrest and cell death in some cancer cell lines (Kefas et al, 2008;Webster et al, 2009). miRNA expression profiling revealed that miR-7 was involved in tumor aggressiveness, invasion and metastasis in urothelial carcinomas and breast cancer (Foekens et al, 2008;Veerla et al, 2009).…”
Section: Pro-metastatic Mirnas Regulate Tumor Metastasismentioning
confidence: 99%